Endoscopic third ventriculostomy may have long term efficacy in low birth weight preterm newborns - de Oliveira, Matheus Fernandes; Nishikuni, Koshiro; Rotta, José Marcus (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2013)
Endoscopic third ventriculostomy (ETV) is an established treatment for hydrocephalus and is an alternative method avoiding shunts and its complications. There is still controversy regarding the higher risk of failure in younger infants. NARF was a male preterm newborn of 33 weeks old, with Moebius syndrome and 1,800 grams at birth. Detailed neonatal evaluation revealed hydrocephalus with bilateral ventricular index of 0.6. It was then decided, in spite of prematurity and low birth weight to perform ETV with the age of 25 days, with 1,850 grams. After discharge, follow-up was lost due to family moving to another city. By chance, after seven years child returned to our medical facility and a follow-up magnetic resonance revealed pervious ETV with high flow, demonstrating functionality of ventriculostomy. Patient's age and etiology of hydrocephalus are the most important factors influencing the success rate of ETV. Recently, the age between 6 months and 1 year old became a cutoff below which failure rates are reported to be particularly high and there are dichotomized experience. The results in low birth weight and preterm infants is not widely known and can be poor. Our case illustrates a successful ETV in a both preterm and low birth weight newborn and a satisfactory long term result, reinforcing the security and efficacy of ETV even in newborns.
Keywords: Third ventricle/surgery; infant newborn; neuroendoscopy